THE ECOLOGICAL CRISIS OF THE 21ST CENTURY: CONSIDERATIONS FROM THE PHILOSOPHY OF VITTORIO HÖSLE - Frazão, Camila Giovanna Xavier de Oliveira; Brasil, Deilton Ribeiro (Revista Direitos Sociais e Políticas Públicas (UNIFAFIBE), 2025)
This paper seeks to investigate the four pillars of the ecological crisis experienced on the planet throughout the 21st century, baring its consequences for vulnerability status groups, seeking to offer necessary answers to overcome current global environmental problems. The work uses the descriptive-analytical method, through bibliographic research, using the reading of articles and books, with the purpose of demonstrating that the democratic system has been used as a maneuver mass to feedback power structures, keeping the status quo in the hands of groups that have profited from the violation of the environment for decades.